Fabrication and characterization of the Mo/cu bimetal with thick Mo layer and high interfacial strength. (January 2021) - Liu, Kaiyuan; Chen, Pengwan; Feng, Jianrui; Ran, Chun; Wang, Yuanjing; Zhou, Qiang; Zhu, Lei
Abstract: Due to the brittleness of molybdenum (Mo) and high difference in melting point, it is still a challenge to clad thick Mo onto copper (Cu) with high quality bonding. In this study, a 5 mm thick Mo plate was successfully welded with Cu plate by hot explosive welding, without any cracks being formed. The maximum shear strength of the interface exceeded 295 MPa. The calculated weldability window indicated that the welding was achieved with the parameters close to the lower boundary, and successfully predicted the wavy interfaces. The interfacial microstructures were investigated by scanning electron microscope, electron backscatter diffraction and transmission electron microscopy, the results showed that the dislocations in Cu were higher than the Mo side and the evolutions of interfacial structure due to severe deformation, such as misorientation angle, recrystallization and texture, were quite different for Mo and Cu. Highlights: Crack-free MoCu bimetal with 5 mm thick Mo was fabricated by hot-explosive welding. The maximum shear strength of the interface reaches 295 MPa. The dynamic recrystallization occurred in Cu and induced by severe deformation. Cu accumulated more dislocation than Mo, and strong texture was formed in Cu.